Reflections on medicalization in education: Perspectives of school psychology and human rights - Silva, Gabriela Machado; de Lima, Cláudia Araújo (Seven Editora, 2024)
The phenomenon of medicalization in education has been a growing concern due to the increase in diagnoses and the use of medications among school-age children. The medicalization of school life often results in a reductionist approach, ignoring the social, political, and cultural factors that influence student learning and behavior. In addition, medicalization can lead to exclusion, labeling and treating students differently, reinforcing stigmas and isolating them from their peers.The formulation of generalized diagnoses, based on standardized and widely disseminated symptoms, can disregard the individual particularities of children, their environment and the issues that involve them during the process of development in childhood. School medicalization, which connects neurological problems to school failure or inappropriate behavior, has become common in schools and health services.To address this issue in a more conscious and equitable way, it is essential to adopt a broader and more contextualized perspective, considering the social, political, and cultural aspects that influence the teaching-learning process. Promoting inclusive education, which respects diversity and human rights, is essential to ensure a healthy and welcoming school environment for all students. Critical reflection on medicalization in education is an important step towards more conscious and equitable pedagogical practices.According to this, this work proposes an in-depth investigation on medicalization in education, in order to provide a critical analysis to deal with the challenges arising from this phenomenon. By adopting a critical and interdisciplinary approach, it seeks not only to understand the causes and consequences of medicalization, but also to promote a more inclusive and rights-based education, which meets the needs of students in a more comprehensive and contextualized way. DOI:https://doi.org/10.56238/sevened2024.015-020